2021
DOI: 10.1139/geomat-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring five indicators for the quality of OpenStreetMap road networks: a case study of Québec, Canada

Abstract: OpenStreetMap (OSM) is one of the most well-known volunteered geographic information (VGI) projects that aims to produce a free-world map. However, there are serious concerns about its quality. Numerous studies have assessed the quality of OSM by comparing the OSM database with a reference database. Several researchers have proposed the use of quality indicators as variables that can describe OSM quality in regions where no reference data are available. A quality indicator is a variable that has a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Our results showed that the challenges of road mapping completeness, including factors such as user interest and the speed of road construction, are particularly pronounced in remote regions with low human influence, like boreal Canada. The quality of OSM road data largely varies due to differences in mapping accuracy and completeness across regions and user contributions 39 . Smaller OSM communities in certain areas result in fewer updates and additions to the road database, particularly in remote or relatively intact regions 35 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the challenges of road mapping completeness, including factors such as user interest and the speed of road construction, are particularly pronounced in remote regions with low human influence, like boreal Canada. The quality of OSM road data largely varies due to differences in mapping accuracy and completeness across regions and user contributions 39 . Smaller OSM communities in certain areas result in fewer updates and additions to the road database, particularly in remote or relatively intact regions 35 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, geographic data generation for OSM primarily involved the use of global positioning system (GPS) receivers to capture coordinates for upload to the database. With the advent of Bing map aerial imagery made available to OSM in November 2010, users were empowered to generate data through the digitization of aerial photographs as well [4].…”
Section: Introductionmentioning
confidence: 99%
“…In regions where authoritative data are lacking, the feasibility of conducting quality assessments of OpenStreetMap (OSM) through direct comparison with such data is limited. This challenge has prompted researchers to investigate alternative methods, seeking quality indicators that can offer insights into the OSM quality in these data-scarce areas [15,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%